TRAUMATIC INJURIES PRESENTING TO THE EMERGENCY DEPARTMENT IN A LEVEL-1 - ALRASHIDI, NASSER (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Traumas are a major health concern in Saudi Arabia, and they can result in many injuries burden. Furthermore, it is one of the main causes of morbidity and mortality in the worldwide. As a result, the awareness of physicians who are the first to see trauma is critical. The study aims to determine the prevalence of traumatic injuries in emergency department. Methods: It is a retrospective study that used the trauma registry of the King Abdulaziz Medical City, Trauma Center to analyze data from January 2015 to January 2020 on trauma patients admitted to the hospital. Demographic features, date and time of admission, type and mechanism of injury, patterns of transportation, and rates of severity were analyzed. p<0.05 was considered statistically significant. Results: A total of 6095 patients, the majority were male (79.9%). Blunt trauma was the most prevalent type of injury (85.7%, p<0.001). A motor vehicle accident was the most prevalent mechanism of injury (37.5%). The highest proportion of trauma per age group was in the 21–30 year age group (28.7%). The mean of Injury Severity Score in the current study was found to be 10.7 and the injured patients’ Glasgow coma scale (GCS) mean was 13.4. The ICU stay average was 3.6 days while the hospital stay was 17.2 days. Conclusion: This study revealed trauma injury patterns in a tertiary hospital in Riyadh, Saudi Arabia, demonstrating the local variation across genders, age groups, types of injury, and mechanisms of injury. These demographic data would be useful for local resourcing of the healthcare system to full impact.